Threatening & protecting press publishers and journalism in the UK's regulation of social media platforms. - Gerbrandt, Ricki-Lee (Journal of Media Law, 2025)
The Online Safety Act 2023 raises concerns about threats to media freedom and the public's access to high-quality news. Those concerns include platform censorship of journalistic content, the proliferation of disinformation and 'extreme' content, abuse targeting journalists, the impact of provisions breaking encryption, journalistic source privilege, and access to information. In confronting those issues, Parliament had to consider several difficult questions, mainly: what is 'journalism' in the digital era? Should a 'recognised news publisher' receive special privileges over all other online speakers? And what is the worry if the state creates a list of publishers and content to privilege? This paper critiques the OSA's treatment of the press and journalism. It defends an institutional protection for the press based on ethical processes of journalism and identifies the need for a principled approach to moderating journalistic content. This will help protect media freedom and an informed public in the digital era.